Effective Microorganism-4 (EM-4) pada Proses Bioremediasi Limbah Cair Industri Tahu - Yuli Patmawati; Alwathan Alwathan; Ikhsanul Akmal Azizi (MEDIA PERSPEKTIF : Journal of Technology, 2021)
Tofu industrial wastewater has a Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) value exceeding the environmental quality standards. The high value of COD and TSS of tofu industrial wastewater is caused by the high content of organic matter and if there is no treatment, the liquid waste of the tofu industry can cause pollution in the aquatic environment. One of the  biological processing of tofu industrial wastewater is the bioremediation process using microorganisms. This study aims to determine the ability of the effective microorganisme-4  (EM-4) on  reduction  of COD and TSS in tofu industrial wastewater. This research was conducted by mixing tofu industrial wastewater and effective microorganism-4 solution into the reactor with various concentrations of EM-4 3%, 5%, 7% and 10% and residence time for 2 days, 4 days and 6 days. The parameters were measured of COD, TSS and pH. The results showed that the tofu industrial wastewater treatment using EM-4 solution with a concentration of 10% for 6 days gave the best results, namely a decrease in COD by 70%, an increase in pH to 8.36 and TSS by 180 mg/L